The Effect of Using Assessment Instruments on Substance-abuse Outpatients' Adherence to Treatment: a Multi-centre Randomised Controlled Trial - Broekaert Eric; De Bacquer Dirk; De Jong Cor AJ; Raes Veerle; De Maeseneer Jan (BMC, 2011)
Abstract Background Drop-out is an important problem in the treatment of substance use disorder. The focus of this study was to investigate the effectiveness of within treatment assessment with feedback directly to patients with multiple substance use disorder on outpatient individual treatment adherence. Feedback consisted of personal resources' and readiness to change status and progress that facilitate or hinder change, thereby using graphical representation. Methods Informed consent was obtained from both the control and experimental groups to be involved in research and follow-up. Following Zelen's single consent design, baseline participants (n = 280) were randomised (sample-size-estimation: 80%power, p=.05, 2-sided) and treatment consent was obtained from those allocated to the experiment (n = 142). In both groups, equal numbers of patients did not attend sessions after allocation. So, 227 persons were analyzed according to intention-to-treat analysis (ITT: experiment n = 116;control n = 111). Excluding refusals 211 participants remained for per-protocol analysis (PP: experiment n = 100; control n = 111), The study was conducted in five outpatient treatment-centres of a large network (De Sleutel) in Belgium. Participants were people with multiple substance use disorder -abuse and dependence- who had asked for treatment and who had been advised to start individual treatment after a standardised admission assessment with the European Addiction Severity Index. The experimental condition consisted of informing the patient about the intervention and of subsequent assessments plus feedback following a protocol within the first seven sessions. Assessments were made with the Readiness to Change Questionnaire and the Personal Resources Diagnostic System. The control group received the usual treatment without within treatment assessment with feedback. The most important outcome measure in this analysis of the study was the level of adherence to treatment at and beyond eight sessions. Results Individual treatment that included assessment with feedback increased adherence to treatment at and beyond eight sessions (RR = 1.6,95%CI:1.2-2.2). Benefit was also found at and beyond twelve sessions, which was the number of sessions required to complete 90% of the assessments with feedback in practice (RR = 1.6,95%CI:1.2-2.5). Conclusions Assessment with feedback in routine practice improved adherence to treatment. More research is needed to evaluate progress in social functioning and motivation to change in outpatient treatment of substance use disorder, thereby using objective measures Trial registration Current Controlled Trials ISRCTN65456186